2015
DOI: 10.1111/appy.12209
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of aggression in hospitalized patients with schizophrenia in China: A meta‐analysis

Abstract: Aggressive behaviour is common in Chinese inpatients with schizophrenia. The prevalence figures indicate the need to identify reliable clinical and illness predictors for aggression in inpatient psychiatric wards and to test investigations aimed at reducing aggressive episodes and their adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 35 publications
4
40
2
Order By: Relevance
“…In our study, the overall prevalence of aggressive behavior among schizophrenia patients was higher than that in the study done in Canada (14.8%) [17], Nigeria (21.9%) [26], and Aro Neuropsychiatric Hospital (23.94%) [27], 5 BioMed Research International respectively. Meta-analysis of published literature indicated that the prevalence of aggressive behavior in schizophrenia patients ranged from 6% to 28% [15] and was lower than the study done in China which ranged between 15.3% and 53.2% with pooled prevalence of aggression 35.4% (95% CI: 29.7%, 41.4%) [16]. The possible reason for the difference in the magnitude of prevalence can be due to the sociocultural difference in the study population, clinical-related factors, and methodological differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the overall prevalence of aggressive behavior among schizophrenia patients was higher than that in the study done in Canada (14.8%) [17], Nigeria (21.9%) [26], and Aro Neuropsychiatric Hospital (23.94%) [27], 5 BioMed Research International respectively. Meta-analysis of published literature indicated that the prevalence of aggressive behavior in schizophrenia patients ranged from 6% to 28% [15] and was lower than the study done in China which ranged between 15.3% and 53.2% with pooled prevalence of aggression 35.4% (95% CI: 29.7%, 41.4%) [16]. The possible reason for the difference in the magnitude of prevalence can be due to the sociocultural difference in the study population, clinical-related factors, and methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in China shows that the prevalence of aggressive behavior in psychiatric wards ranged between 15.3% and 53.2%. The pooled prevalence of aggression was 35.4% (95% CI: 29.7%, 41.4%) [16].…”
Section: Prevalence Of Aggressive Behavior Among People Withmentioning
confidence: 98%
“…The prevalence of violent offenses in schizophrenic patients is higher than that of the general population ( 2 4 ). In China, meta-analysis from our group showed, the prevance of aggression of inpatients with schizophrenia was 35.4% (95% CI: 29.7%, 41.4%) ( 5 ). Although the etiology of violent and aggressive behavior in schizophrenia is multifactorial, genetic inheritance may strongly contribute to it ( 4 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 98%
“…2 The incidence of violent behavior in Chinese psychiatric wards is 15.3%-53.2% among 3941 schizophrenic patients. 3 Studies from 10 countries in Europe illustrate the number of violent behavior of patients around 16-42% in some acute psychiatric and forensic services. 4 Acute psychiatric wards treat patients with emergency criteria that threaten and endanger health, safety, and the environment from their violent behavior.…”
Section: Introductionmentioning
confidence: 99%